Price asymmetry in farm-retail price transmission in the Turkish dairy market - Özgür Bor; Mustafa İsmihan; Ahmet Bayaner (Turkish Economic Association, 2013)
This study investigates the price asymmetry in farm-retail price transmission in the Turkish milk market. An asymmetric error correction model is applied on the monthly price data, and the results suggest that there is a positive price asymmetry in the farm-retail price transmission in the Turkish dairy market. That is, the retail prices tend to adjust more quickly to the input price increases than to its decreases which yield welfare losses to the consumers. In addition, cointegration results imply that there is a significant market power in the dairy market.
Keywords: 330; Price Asymmetry; Turkey; Milk; Error Correction Model